Sprout - Lee, Eugene Joon Kiat (2019)
Effective use of water has been becoming increasingly important in Singapore where natural resources such as water is scarce. Due to land constraints, there is limited land area to harvest rainwater. The utilization of the water catchment areas has increased from half to two-thirds of the island since 2011 (Public Utilities Board, n.d.). Despite the large land area, the water harvested from the reservoirs is inadequate to meet our needs (Tortajada, 2016). Since Singapore does not have self-sufficient means to harvest water, it is necessary that Singaporeans adopt a practice of harvesting and making use of rainwater efficiently. Currently, there is no Rainwater Harvesting System (RHS) in public housing for residential use. According to the author’s conducted interviews and investigations, most residents rely only on pails to harvest rainwater. This method of harvesting rainwater is inefficient as it may promote mosquito breeding and might become a possible source of danger if the pails are placed in an unsuitable location. Through this project, the author aims to design a product that enables residents to harvest rainwater efficiently and utilize the water at the point of need. By harvesting rainwater for non-potable uses, we can conserve our valuable resources, reduce the wastage of water and saving money by spending less on water. This project was awarded MERIT for the Singapore Creator Awards 2019 and BRONZE for the ADM Sustainability Award 2019.